Enhancing Microhardness and Corrosion Resistance of Anodic Oxides Grown on Hypoeutectic Al–Si Alloys Pretreated by Low-Energy High-Current Electron Beams; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 18, iss. 5 - Huspek A. L. Lucchini; Akdogan B.; Akhmadeev Yu. Kh. Yury Khalyafovich; Petrikova E. A. Elizaveta Alekseevna; Ivanov Yu. F. Yury Fedorovich; Moskvin P. V. Pavel Vladimirovich; Koval N. N. Nikolay Nikolaevich; Bestetti M. Massimiliano (2024, 2024)
Title screen